Kontribusi Warisan Nilai-Nilai Kerajaan Islam Terhadap Pembentukan Pancasila di Nusantara - Wulandari, Yunita; Zahro’, Khurun’in; Hidayah, Akmal (Proceedings of Annual Conference for Muslim Scholars, 2023)
Pancasila is the Republic of Indonesia's fundamental philosophy. Before entering the colonial period, it formed and molded from many characteristics and influences of the Islamic Kingdom. The rise of the Islamic Kingdom had an impact on the values of Indonesian society. This research focuses on the legacy of Islamic Kingdom values in the establishment of Pancasila in Indonesia. The purpose of this study is to examine the creation of Pancasila through the lens of the Islamic Kingdom's heritage values in the archipelago/Indonesia. This is a qualitative method with a historical study, the data taken from some literature and historical book. As a result, the principles of social life throughout the Islamic Kingdom influenced each precept. There were numerous forms of Pancasila value creation, resulting in a synthesis of the values inherited by the Islamic Kingdom in the formation of the state ideology, namely is Pancasila.